Effects of doxycycline on prepatent and patent infections of Brugia pahangi in dogs and observations on the growth and survival of L3 in jirds and dogs - John W. McCall; Laura Kramer; Claudio Genchi; Jorge Guerrero; Michael T. Dzimianski; Abdelmoneim Mansour; Scott McCall; Ben Carson; Christopher C. Evans (Veterinary Parasitology, 2025)

3D Numerical Model of the Thermal Interaction Between Sediment–Water–Atmosphere - Alejandro J. Vitale; M. Cintia Piccolo; Sibila A. Genchi; Claudio A. Delrieux; Gerardo M. E. Perillo (Environmental Modeling & Assessment, 2014)

Detection of Dirofilaria immitis in mid-western arid Argentina - Pablo Cuervo; Roberto Mera y Sierra; Viviana Waisman; Leticia Gerbeno; Laura Sidoti; Francesca Albonico; Mara Mariconti; Michele Mortarino; Paola Pepe; Giuseppe Cringoli; Claudio Genchi; Laura Rinaldi (Acta Parasitologica, 2013)
Dirofilariosis, caused by Dirofilaria immitis and D. repens, is (re-) emerging worldwide. Dogs are the main reservoirs, while human infection has recently become an important focus of interest and attention. In Argentina, canine D. immitis infection has been described in eastern and northern subtropical and temperate humid regions, but never reported in mid-western arid regions so far. In this research note we report for the first time the occurrence of autochthonous human and canine D. immitis infection in the region.

Asaia , a versatile acetic acid bacterial symbiont, capable of cross‐colonizing insects of phylogenetically distant genera and orders - Elena Crotti; Claudia Damiani; Massimo Pajoro; Elena Gonella; Aurora Rizzi; Irene Ricci; Ilaria Negri; Patrizia Scuppa; Paolo Rossi; Patrizia Ballarini; Noura Raddadi; Massimo Marzorati; et al. (Environmental Microbiology, 2009)
Summary Bacterial symbionts of insects have been proposed for blocking transmission of vector‐borne pathogens. However, in many vector models the ecology of symbionts and their capability of cross‐colonizing different hosts, an important feature in the symbiotic control approach, is poorly known. Here we show that the acetic acid bacterium Asaia , previously found in the malaria mosquito vector Anopheles stephensi , is also present in, and capable of cross‐colonizing other sugar‐feeding insects of phylogenetically distant genera and orders. PCR, real‐time PCR and in situ hybridization experiments showed Asaia in the body of the mosquito Aedes aegypti and the leafhopper Scaphoideus titanus , vectors of human viruses and a grapevine phytoplasma respectively. Cross‐colonization patterns of the body of Ae. aegypti , An. stephensi and S. titanus have been documented with Asaia strains isolated from An. stephensi or Ae. aegypti , and labelled with plasmid‐ or chromosome‐encoded fluorescent proteins (Gfp and DsRed respectively). Fluorescence and confocal microscopy showed that Asaia , administered with the sugar meal, efficiently colonized guts, male and female reproductive systems and the salivary glands. The ability in cross‐colonizing insects of phylogenetically distant orders indicated that Asaia adopts body invasion mechanisms independent from host‐specific biological characteristics. This versatility is an important property for the development of symbiont‐based control of different vector‐borne diseases.

wsp Gene Sequences from the Wolbachia of Filarial Nematodes - Chiara Bazzocchi; Wanwisa Jamnongluk; Scott L. O'Neill; Tim J.C. Anderson; Claudio Genchi; Claudio Bandi (Current Microbiology, 2000)